Cu-catalysed direct C–H (hetero)arylation of [1, 2, 4]triazolo[4, 3-a]pyridine to construct deep-blue-emitting luminophores1. Issue 19 (21st May 2015) - Wu, Jie; You, Qiulin; Lan, Jingbo; Guo, Qiang; Li, Xiaoyu; Xue, Ying; You, Jingsong
<x xml:space="preserve">Abstract</x> An efficient protocol for the synthesis of 3-aryl-[1, 2, 4]triazolo[4, 3-a]pyridines has been developed via Cu-catalysed direct C–H (hetero)arylation. The resulting compounds exhibit deep-blue emission with high quantum yields, photostability, and thermal stability.